Solid electrolyte, positive electrode, electrolyte layer, and secondary battery
By using the oxide represented by the general formula Li6-xR1-y-aAy-bMx(BO3)3 as the solid electrolyte and sintered at low temperature, the problem of insufficient ion conductivity of the solid electrolyte at low temperature is solved, and high ion conduction is achieved and low resistance effects.
Patent Information
- Application Number
- CN202380049996.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-09
- Publication Date
- 2025-02-14
AI Technical Summary
The existing solid electrolytes are insufficient ion conductivity at low temperatures, and high temperature sintering may lead to the formation of high-resistance phases, limiting the improvement of ion conductivity.
The oxide represented by the general formula Li6-xR1-y-aAy-bMx(BO3)3 is used as the solid electrolyte, where R is a rare earth element of Yb, Er, Ho, Tm and La, and A is Al, Fe, Mn and Ga. Metal elements, M are tetravalent elements of Zr and Ce, and are produced by low-temperature sintering.
The production of high ion conductivity solid electrolytes at low temperatures is achieved, reducing the formation of high resistance phases and improving the performance of secondary batteries.
Smart Images

Figure CN119452430A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte, a positive electrode, an electrolyte layer and a secondary battery comprising the same. Background Art
[0002] All-solid-state secondary batteries containing solid electrolytes can have higher heat resistance and improved safety because the electrolyte does not leak or volatilize. Therefore, module costs can be reduced and energy density can be increased.
[0003] As one of such solid electrolytes, sulfide-based solid electrolytes have been reported. However, sulfide-based solid electrolytes have problems in processability because sulfide is used as a raw material for its production. Therefore, oxide-based solid electrolytes have been reported as non-sulfide-based solid electrolytes.
[0004] As Li-containing solid electrolytes, NASICON-type Li1+xAlxTi 2-x (PO4)3(LATP), perovskite-type Li 3+x La 2 / 3-x TiO3(LLT) and garnet-type cubic Li7La3Zr2O 12 As a solid electrolyte containing Na, β″-alumina-type Na2O· (5-7) Al2O3 and NASICON type Na3Zr2Si2PO 12 However, these solid electrolytes have the following problems: the available negative electrode materials are limited, and sintering at a high temperature of more than 1000°C is required to improve conductivity by bringing the interfaces between the solid electrolytes and between the solid electrolytes and the active material into close contact with each other. In particular, high-temperature sintering may cause the formation of a high resistance phase between the solid electrolytes and at the interface between the solid electrolyte and the active material, thereby limiting the improvement of ion conductivity.
[0005] For these reasons, attempts have recently been made to lower the sintering temperature. Patent Document 1 discloses that by using a Li 2+x C 1-x B x Solid electrolytes containing lithium borate, such as O3, can reduce the post-baking temperature to about 900°C.
[0006] Patent Document 2 states that mixing Li 3 BO 3 with LLZ-type oxides can reduce the sintering temperature to 650° C. to 800° C. when forming a solid electrolyte.
[0007] Citation List
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Laid-Open No. 5-54712
[0010] Patent Document 2: Japanese Patent Laid-Open No. 2013-37992 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] In the secondary battery containing each solid electrolyte disclosed in Patent Documents 1 and 2, a low post-baking temperature is used, and a high resistance phase is not easily formed as an intermediate layer at the interface with other materials. However, in some cases, the ion conductivity σ of the area occupied by the corresponding solid electrolyte at room temperature is SE Less than 1×10 -7 S / cm. There is a demand for oxide-based solid electrolytes with enhanced ionic conductivity.
[0013] An object of the present invention is to provide a solid electrolyte having high ion conductivity that can be produced by sintering at a low temperature, and a positive electrode, an active material layer, and a secondary battery including the solid electrolyte.
[0014] Solutions for solving problems
[0015] The solid electrolyte according to an embodiment of the present invention contains the general formula Li 6-x R 1-y-a A y-b M x Oxide represented by (BO3)3.
[0016] Here, R is at least one or two elements selected from the group consisting of trivalent elements Yb, Er, Ho, and Tm, A is an element selected from Al, Fe, Mn, and Ga, M1 is a tetravalent element, x and y are real numbers satisfying 0<x, y<1, and a and b are real numbers satisfying a+b=x. A solid electrolyte according to an embodiment of the present invention includes a borate containing Li, an element R selected from Yb, Er, Ho, Tm, and La, an element A selected from Al, Fe, Mn, and Ga, and an element M selected from Zr and Ce.
[0017] The solid electrolyte according to an embodiment of the present invention contains a borate, which contains Li, an element R selected from Yb, Er, Ho, Tm, and La, an element A selected from Al, Fe, Mn, and Ga, and an element M selected from Zr and Ce. In X-ray diffraction analysis using Cu Kα rays, the solid electrolyte exhibits two diffraction peaks in the range where the diffraction angle 2θ is 28.0° or more and 29.0° or less, and the diffraction angle difference 2θd between the high-angle side diffraction peak and the low-angle side diffraction peak is 0.416° or more.
[0018] The solid electrolyte according to an embodiment of the present invention contains an oxide represented by the general formula Li 6-x R 1-y-a A y-b M x (BO3)3, where, in the formula, R is at least one or two elements including rare earth elements selected from Yb, Er, Ho, Tm, and La, A is a metal element selected from Al, Fe, Mn, and Ga, M is a tetravalent element, x and y are real numbers satisfying 0 < x, y < 1, and a and b are real numbers satisfying a + b = x. The solid electrolyte contains an oxide represented by the general formula Li 6-x R 1-y-a A y-b M x (BO3)3, where, in the formula, R is a rare earth element selected from Yb, Er, Ho, Tm, and La, A is a metal element selected from Al, Fe, Mn, and Ga, M is an element selected from Zr and Ce, x and y are real numbers satisfying 0 < x, y < 1, and a and b are real numbers satisfying a + b = x.
[0019] Effects of the Invention
[0020] According to the present invention, a solid electrolyte having high ionic conductivity that can be produced by low-temperature sintering and a secondary battery containing the solid electrolyte can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a graph showing the relationship between the ionic conductivity of each of the solid electrolytes according to Examples 1 to 17 included in the first embodiment and the value of the composition x (x1 + x2) of the substitution element M.
[0022] Figure 2 is a graph showing the relationship between the ionic conductivity of each of the solid electrolytes according to Examples 1 to 17 included in the first embodiment and the value of the composition y of the substitution element A.
[0023] Figure 3 shows the diffraction curves of the solid electrolytes according to Examples 1 to 14.
[0024] Figure 4 Shows the diffraction curves of the solid electrolytes according to Embodiments 15 to 17.
[0025] Figure 5 Shows the diffraction curves of the solid electrolytes according to Embodiments 1 to 8.
[0026] Figure 6 Shows the diffraction curves of the solid electrolytes according to Embodiments 12 to 14.
[0027] Figure 7 Shows the diffraction curves of the solid electrolytes according to Embodiments 15 to 17.
[0028] Fig. 8A Is a schematic cross-sectional view of a secondary battery according to a second embodiment.
[0029] Figure 8B Is a partial enlarged view of the positive electrode and the electrolyte layer of the secondary battery according to the second embodiment. Detailed Description of the Invention
[0030] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0031] (First Embodiment)
[0032] The solid electrolyte contains an oxide represented by the general formula Li 6-x R 1-y-a A y-b M x (BO3)3.
[0033] In the formula, R is an element selected from Yb, Tm, Ho, Er, and La, A is an element selected from Al, Fe, Mn, and Ga, and M is a tetravalent element selected from Zr and Ce. Further, a and b are real numbers satisfying 0 ≤ a, b < 1 and a + b = x; and x and y are real numbers satisfying 0 < x, y < 1.
[0034] In the formula, when R includes at least two elements selected from the trivalent elements Yb, Er, Ho, Tm, and La, the element may be combined with other trivalent elements having an ionic radius close to the elements selected from Yb, Er, Ho, Tm, and La.
[0035] In other words, the solid electrolyte according to the present embodiment contains an oxide represented by the general formula Li 6-x R 1-y-a A y-b M x (BO3)3.
[0036] In the formula, R is at least one or two rare earth elements selected from Yb, Er, Ho, Tm, and La; A is an element selected from Al, Fe, Mn, and Ga; M is an element selected from Zr and Ce. In addition, a and b are real numbers satisfying 0 ≤ a, b < 1 and a + b = x; and x and y are real numbers satisfying 0 < x, y < 1.
[0037] In the formula, when R contains at least 2 elements selected from the group including the rare earth elements Yb, Er, Ho, Tm, and La, combinations of rare earth elements in this group can be used, and combinations of other rare earth elements with ionic radii close to these elements can also be used.
[0038] The possible reasons for improving the ionic conductivity of the solid electrolyte containing the oxide represented by the above general formula will be described below.
[0039] When the rare earth elements Yb, Er, Ho, Tm, and La are partially replaced by the tetravalent element M, the charge balance is adjusted in such a way that the whole crystal is neutral, thereby creating a state of Li deficiency in the lattice. The part lacking the element is usually called a vacancy. The phenomenon that Li around the vacancy moves towards the vacancy (usually called hopping) occurs in a cooperative manner, thereby improving the ionic conductivity. In this case, it is considered that by replacing a part of the rare earth elements Yb, Er, Ho, Tm, and La with Al, Fe, Mn, and Ga which are metal elements A with the same trivalence, changes occur in the lattice. At this time, it is considered that the vacancy serving as the path for Li ions becomes a size suitable for Li ion movement. + In the general criterion for element substitution, it is considered that an atomic radius within ±15% is appropriate. However, the atomic radii of the above rare earth element R and metal element A are outside this criterion, so it is considered difficult to perform substitution. However, although the stabilization mechanism has not been verified, as shown by the XRD comparison results of + and + before and after substitution, the crystal structure did not change and no impurities were detected; therefore, in this compound, the rare earth element R is replaced by the metal element A. It is speculated that because substitution is carried out by elements with such a large difference in atomic radius, the lattice also changes, thereby effectively forming the path of the above Li. + In other words, the solid electrolyte of this embodiment is a solid electrolyte containing borate, and the borate contains Li, an element R selected from Yb, Er, Ho, Tm, and La, an element A selected from Al, Fe, Mn, and Ga, and an element M selected from Zr and Ce.
[0040] Figure 3 Figure 4 and
[0041] + ions.
[0042] The solid electrolyte of the present embodiment preferably has a monoclinic crystal structure.
[0043] In X-ray diffraction analysis (hereinafter, referred to as “XRD”) using Kα rays of copper, a diffraction peak at a diffraction angle 2θ of about 28° varies depending on the composition of the solid electrolyte.
[0044] The oxides are of the general formula Li 6-x R 1-y-a A y-b M x The solid electrolyte of the present embodiment represented by (BO3)3 (wherein R is Yb and A is Al) preferably exhibits a diffraction peak in the range of 2θ=28.0° to 28.20° in XRD using copper Kα rays. More preferably, the solid electrolyte has a peak in the range of 2θ=28.10° to 28.20°.
[0045] In XRD using Kα rays of copper, the position of the diffraction peak at about 2θ=28° can be controlled by adjusting the value of x in the general formula and changing the element represented by M.
[0046] In the above general formula, M is a tetravalent element and is at least one element selected from Zr and Ce.
[0047] As elements replacing Yb, Er, Ho, Tm and La as the trivalent element R, elements with similar ionic radius are easily substituted. Specific examples thereof include Zr 4+ 、Ce 4+ Sn 4+ 、Ti 4+ , Nb 4+ , Pb 4+ , Pr 4+ , and Nb 5+ As a candidate. Among them, Zr 4+ and Ce 4+ Easier to replace.
[0048] In the general formula, a and b are real numbers satisfying 0 ≤ a, b < 1 and a + b = x; and x and y are real numbers satisfying 0 < x, y < 1. a and b respectively correspond to the ratios of the element R and the element A replaced by the replacing element M. The ratios of the element R and the element A replaced by the replacing element M can be freely selected. The ratio of the replacing element M is preferably the same as the ratios of the element R and the element A. That is, preferably a:b = [R]:[A]. As x corresponding to the replacement amount of the replacing element M for the element R, a value of 0.025 or more and 0.4 or less is used. As a more preferable x, a value of 0.050 or more and 0.227 or less is used. a and b respectively represent the ratios of the element R and A replaced by the replacing element M. As y corresponding to the replacement amount of the element R for the element A, a value of 0.05 or more and 0.50 or less is used. As a more preferable y, a value of 0.010 or more and 0.200 or less is used.
[0049] The reason for preferably selecting the above range of x is inferred as follows: When the value of x is less than 0.025, since the amount of the element R to be replaced is small, sufficient structural defects do not occur, and the path through which Li + ions pass is not sufficiently formed, resulting in no improvement in ionic conductivity. When the value of x is greater than 0.4, the amount of the replacing element M is too large. Therefore, the excessive element M that does not contribute to the replacement of the element R in the crystal contributes as an inhibitory component for ionic conduction rather than the replacement effect in the crystal.
[0050] The reason for preferably selecting the above range of y is inferred as follows: When the value of y is less than 0.050, since the amount of the element R to be replaced is small, sufficient structural changes do not occur, and the path through which ions pass is not changed to an appropriate size, resulting in no improvement in ionic conductivity. When the value of y is greater than 0.50, the amount of the replacing element A is too large. Therefore, the excessive element A that does not contribute to the replacement of the element R in the crystal contributes as an inhibitory component for ionic conduction rather than the replacement effect in the crystal.
[0051] Hereinafter, the production method of the solid electrolyte of the present embodiment will be described.
[0052] The production method of the solid electrolyte of the present embodiment includes: heating Li, R, A, and M, which are elements of the solid electrolyte represented by the oxide Li 6-x R 1-y-a A y-b M x (BO3)3, or their oxides in an oxygen-containing atmosphere in a post-calcination step (wherein, R is at least one or two elements selected from the rare earth elements Yb, Er, Ho, Tm, and La, A is an element selected from Al, Fe, Mn, and Ga, and M is a tetravalent element).
[0053] The method for producing a solid electrolyte of the present embodiment includes a pre-baking step of solid-phase synthesizing the oxide represented by the above general formula by heat treatment at a temperature lower than the melting point of the oxide, and a step of densifying the obtained oxide by heat treatment.
[0054] Hereinafter, although the production method of the solid electrolyte of the present embodiment including the above-mentioned pre-baking step and the above-mentioned post-baking is described in detail, the present invention is not limited to the following production method.
[0055] <Pre-baking step>
[0056] In the pre-calcination step, reagent grade raw materials such as Li3BO3, H3BO3, Yb2O3, Er2O3, Ho2O3, Tm2O3, La2O3, α-Al2O3, Fe2O3, Mn2O3, Ga2O3, ZrO2, and CeO2 are weighed and mixed together with reference to a predetermined stoichiometric ratio to form Li 6-x R 1-y-a A y-b M x (BO3)3. Other raw materials weighed to achieve a predetermined stoichiometric ratio include SnO2 and Nb2O3. Here, R is at least one or two elements selected from rare earth elements Yb, Er, Ho, Tm and La, A is an element selected from Al, Fe, Mn and Ga, and M is a tetravalent element.
[0057] As a device for mixing, in addition to a mortar and pestle, a mixer such as a ball mill can be used.
[0058] After preparing a mixed powder of the above raw materials by mixing treatment, the obtained mixed powder is press-formed into pellets. Here, as a press-forming method, a known press-forming method such as a cold uniaxial forming method or a cold isostatic pressing method can be used. As a condition for press-forming in the pre-baking step, for example, the pressure can be, but is not particularly limited to, 100 to 300 MPa.
[0059] The obtained pellets are pre-baked at 500 to 800° C. using, for example, an atmospheric post-baking apparatus to perform solid phase synthesis. The time of the pre-baking step may be, for example, but not particularly limited to, about 700 to 750 minutes (eg, 720 minutes).
[0060] The obtained pre-calcined body is of the general formula Li 6-x R 1-x M x The oxide represented by (BO3)3. The pre-sintered body can be ground with, for example, a mortar and pestle to prepare a pre-baked powder.
[0061] <Post-calcination step>
[0062] In the post-baking step, at least one selected from the group consisting of the pre-baked body and the pre-baked body prepared in the pre-baking step is pressure-molded and post-baked, thereby preparing a dense sintered body.
[0063] The press forming and post-baking can be performed simultaneously by, for example, spark plasma sintering or hot pressing. Alternatively, after the pellets are produced by cold uniaxial forming, post-baking can be performed, for example, in an air atmosphere. As the conditions for the press forming in the post-baking step, for example, the pressure can be, but is not particularly limited to, 100 to 300 MPa.
[0064] The post-calcination temperature is preferably 800° C. or lower, more preferably 700° C. or lower, still more preferably 680° C. or lower.
[0065] The time of the post-baking step can be appropriately changed depending on, for example, the post-baking temperature, and can be, for example, about 700 to 750 minutes (eg, 720 minutes).
[0066] The cooling method in the post-calcination step is not particularly limited. Natural cooling may be used. Cooling slower than natural cooling may also be used.
[0067] Hereinafter, the secondary battery according to the present embodiment will be described.
[0068] A typical secondary battery includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, an electrolyte including a solid electrolyte disposed between the positive electrode and the negative electrode, and a current collector if necessary.
[0069] The secondary battery of the present embodiment is a secondary battery including at least a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and an electrolyte, and at least one selected from the positive electrode, the negative electrode, and the electrolyte contains the solid electrolyte of the present embodiment.
[0070] In the secondary battery of the present embodiment, the electrolyte may include the solid electrolyte of the present embodiment, or may include other solid electrolytes. Examples of other solid electrolytes that may be included include, but are not particularly limited to, Li3PO4, Li7La3Zr2O 12 , Li 0.33 La 0.55 TiO3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3, and Li 1.3 Al 0.3 Ti 1.7 (PO4)3. The solid electrolyte of the present embodiment is contained in the electrolyte of the secondary battery of the present embodiment in an amount of preferably 25% by mass or more, more preferably 50% by mass or more, still more preferably 75% by mass or more, particularly preferably 100% by mass.
[0071] The secondary battery of the present embodiment can be produced by known methods, for example, by lamination, shaping, and heat treatment of a positive electrode, a solid electrolyte, and a negative electrode. The solid electrolyte of the present embodiment can be produced by heat treatment at a lower temperature than in the prior art, thereby reducing the formation of a high resistance phase caused by the reaction of the solid electrolyte with the electrode active material. This can produce a secondary battery with excellent output characteristics. The "solid" used in this specification includes an object that has a self-supporting property to the extent that it maintains a certain shape and volume even if the posture of the object changes. In other words, the object is non-flowable and has a volume of less than 1×10 7 cP(less than 1×10 4 The viscosity of the
[0072] Hereinafter, the method of measuring physical properties according to the present disclosure will be described.
[0073] Identification of R, A and M
[0074] When the collected sample is not a mixture with other materials, after the collected sample is processed into a solution, the composition ratio of the sample can be identified by, for example, inductively coupled plasma atomic emission spectrometry (ICP-AES) or wavelength dispersive X-ray fluorescence spectrometry (WDXRF). WDXRF can also be called WDX.
[0075] When the possibility that the collected sample is a mixture is high, a scanning analyzer capable of providing elemental mapping images, such as an X-ray photoelectron spectrometer (XPS, ESCA) or a scanning electron microscope equipped with an energy dispersive X-ray fluorescence analyzer (EDXRF) can be used. Hereinafter, a scanning electron microscope equipped with an energy dispersive X-ray fluorescence analyzer (EDXRF) is referred to as SEM / EDX. When the possibility that the collected sample is a mixture is high, a transmission electron microscope (TEM-ED) equipped with an electron beam diffraction function can be used to identify the crystal structure. EDXRF can also be referred to as EDX.
[0076] ICP-AES and XPS were used in order to accurately determine the composition ratio of Li as a light element and other elements with higher atomic numbers such as B, O, Al, Zr, and rare earth elements.
[0077] When the collected sample is a mixture, pretreatment is used to selectively remove non-target parts for analysis by physical removal treatment such as cutting or ion beam processing, chemical removal such as dry etching or wet etching, or a combination thereof. For pretreatment, washing, degreasing, slicing, grinding, or granulation, etc. can be used.
[0078] As for the standard sample, S-4800 available from Hitachi High-Technologies Corporation can be used as an analyzer for SEM / EDX.
[0079] Measurement of X-ray diffraction peaks
[0080] RINT-2100 from Rigaku Corporation was used for X-ray diffraction analysis of the solid electrolyte.
[0081] The powder prepared by grinding the solid electrolyte with a mortar and pestle was subjected to X-ray diffraction analysis using characteristic X-rays of CuKα. The temperature was room temperature, the analysis range was 10° to 70°, the step length was 0.016°, and the scanning speed was 0.5 steps / second.
[0082] (Second embodiment)
[0083] <Structure of secondary battery and positive electrode>
[0084] Reference Fig. 8A and Figure 8B , an electrolyte layer 40 including a solid electrolyte 44 according to the first embodiment and a secondary battery 100 including the electrolyte layer 40 are described.
[0085] Fig. 8A : is a schematic cross-sectional view of a secondary battery 100 including an electrolyte layer 40 using a solid electrolyte 44 of the present embodiment. The secondary battery 100 includes an electrolyte layer 40 on a surface of the positive electrode active material layer 20 opposite to a side where the positive electrode collector layer 10 contacts the positive electrode active material layer 20. The secondary battery 100 includes a negative electrode 70 on a side of the electrolyte layer 40 opposite to a side where the electrolyte layer 40 contacts the positive electrode active material layer 20. The negative electrode 70 includes a negative electrode active material layer 50 on a surface of the electrolyte layer 40 opposite to a surface contacting the positive electrode active material layer 20. The negative electrode 70 includes a negative electrode collector layer 60 on a surface of the negative electrode active material layer 50 opposite to a surface contacting the electrolyte layer 40. In other words, the secondary battery 100 includes a negative electrode 70, an electrolyte layer 40, and a positive electrode 30 in a stacking direction 200.
[0086] like Figure 8BAs shown, the electrolyte layer 40 using the electrolyte 44 of the present embodiment is in contact with the positive electrode 30 including the positive electrode collector layer 10 and the positive electrode active material layer 20 including the active material particles 22 and the positive electrode electrolyte 24. In this specification, a structure configured to receive lithium ions (active material ions) from the electrolyte layer 40 or release lithium ions (active material ions) to the electrolyte layer 40 is referred to as a positive electrode; therefore, the positive electrode active material layer 20, which is a part of the positive electrode 30 other than the positive electrode collector layer 10, may also be referred to as a positive electrode 20, such as Fig. 8A The positive electrode active material layer 20 of this embodiment includes a positive electrode electrolyte 24 , and thus can be referred to as a composite positive electrode active material layer 20 or a composite positive electrode structure 20 .
[0087] The current collector layer 10 is a conductor that conducts electrons between an external circuit (not shown) and the active material layer. As the current collector layer 10, a self-supporting film of a metal such as stainless steel (SUS) or aluminum, or a laminated structure of a metal foil and a resin substrate is used.
[0088] The positive electrode active material layer 20 includes positive electrode active material layers 20a, 20b and 20c as sublayers. The positive electrode active material layers 20a, 20b, 20c are distinguished by stacking units in the layer thickness direction 200 before sintering the active material particles 22 and the positive electrode electrolyte 24. The positive electrode active material layers 20a, 20b, 20c may have a layer thickness distribution in terms of volume fractions of the active material particles 22 and the positive electrode electrolyte 24, a conductive aid (not shown), and void ratio (porosity). The layer thickness direction 200 is parallel or anti-parallel to the stacking direction of the stacked layers, and therefore may also be referred to as the stacking direction 200.
[0089] The solid electrolyte 44 according to the present embodiment is used for the positive electrode electrolyte 24 in the composite positive electrode active material layer 20. The positive electrode electrolyte 24 and the solid field material 44 in the electrolyte layer 40 may have the same composition and particle size distribution, or may have different compositions and particle size distributions.
[0090] (negative electrode)
[0091] As a method for producing the negative electrode, a known method can be used. As in the second embodiment of the present application, the method for producing the positive electrode 30 in the first embodiment can be used with necessary changes to form the negative electrode. Similar to the positive electrode 30, the negative electrode may have a structure in which both the negative electrode active material and the solid electrolyte are contained in a layer, or may be formed of a film composed of a metal such as metal Li or In-Li.
[0092] [Negative electrode active material]
[0093] Examples of the negative electrode active material include metals, metal fibers, carbon materials, oxides, nitrides, silicon, silicon compounds, tin, tin compounds, and various alloy materials. Among them, from the viewpoint of capacity density, metals, oxides, carbon materials, silicon, silicon compounds, tin, and tin compounds are preferred. Examples of metals include metallic Li and In-Li. Examples of oxides include Li4Ti5O 12 (lithium titanate: LTO). Examples of carbon materials include various natural graphites (graphite), cokes, graphitizable carbon materials that have undergone graphitization, carbon fibers, spherical carbon, various artificial graphites, and amorphous carbon. Examples of silicon compounds include silicon-containing alloys, silicon-containing inorganic compounds, silicon-containing organic compounds, and solid solutions. Examples of tin compounds include SnO b (0 < b < 2), SnO2, SnSiO3, Ni2Sn4, and Mg2Sn. The negative electrode material may contain a conductive additive. Examples of conductive additives include graphite, such as natural graphite and artificial graphite, and carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking carbon black. Other examples of conductive additives include conductive fibers, such as carbon fibers, carbon nanotubes, and metal fibers, carbon fluoride, metal powders, such as aluminum, conductive metal oxides, such as conductive whiskers, such as zinc oxide and titanium oxide, and organic conductive materials, such as phenyl-based dielectrics.
[0094] Examples
[0095] Examples of the production and evaluation of the solid electrolyte of the present embodiment as a sintered body are described. The present disclosure is not limited to the following examples.
[0096] [Example 1]
[0097] <Pre-roasting step>
[0098] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Yb2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) are provided as raw materials for the solid electrolyte. In the form of Li 5.95 Yb 0.85 Al 0.045 Zr 0.1 (BO3)3, they are weighed in a predetermined stoichiometric ratio and mixed with a mortar and pestle.
[0099] Thereafter, the mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0100] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0101] <Post-calcination step>
[0102] The pre-calcined powder prepared as described above was molded and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 1. The heating temperature was 670° C. and the holding time was 720 minutes.
[0103] [Examples 2 to 8]
[0104] <Pre-calcination step>
[0105] A pre-calcined body and a pre-calcined powder were produced in the same manner as in Example 1 except that the raw materials described in Example 1 were weighed at a predetermined stoichiometric ratio so that each value became the value shown in Table 1.
[0106] <Post-calcination step>
[0107] The pre-sintered powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body.
[0108] [Examples 9 and 10]
[0109] <Pre-calcination step>
[0110] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Yb2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), ZrO2 (obtained from Nippon Denko Co., Ltd.), and CeO2 (obtained from Iwatani Corporation) were provided as raw materials for the solid electrolyte. The composition after sintering was Li 5.875 Yb 0.7875 Al 0.0875 Zr 0.1 Ce 0.025 (BO3)3 and Li 5.877 Yb 0.7591 Al 0.135 Zr 0.104 Ce0.0186 They were weighed in a predetermined stoichiometric ratio in the manner of (BO3)3 and mixed in a mortar and pestle.
[0111] Thereafter, each mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0112] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0113] <Post-calcination step>
[0114] Each of the pre-calcined powders prepared as described above was molded and heat-treated in the same manner as in the pre-calcination, thereby producing a sintered body of Example 1. The heating temperature was 670° C., and the holding time was 720 minutes.
[0115] [Example 11]
[0116] <Pre-baking step>
[0117] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Yb2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), La2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. The composition after sintering was Li 5.875 Yb 0.7200 La 0.090 Al 0.090 Zr 0.1 They were weighed in a predetermined stoichiometric ratio in the manner of (BO3)3 and mixed in a mortar and pestle.
[0118] Thereafter, the mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0119] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0120] <Post-calcination step>
[0121] The pre-calcined powder prepared as described above was molded and heat-treated in the same manner as in the pre-calcination, thereby producing a sintered body of Example 26. The heating temperature was 670° C., and the holding time was 720 minutes.
[0122] [Example 12]
[0123] <Pre-calcination step>
[0124] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Yb2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), α-Fe2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. The composition after sintering was Li 5.9 Yb 0.81 Fe 0.09 Zr 0.1 They were weighed in a predetermined stoichiometric ratio in the manner of (BO3)3 and mixed in a mortar and pestle.
[0125] Thereafter, the mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0126] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0127] <Post-calcination step>
[0128] The pre-calcined powder prepared as described above was molded and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 1. The heating temperature was 670° C. and the holding time was 720 minutes.
[0129] [Example 13]
[0130] <Pre-calcination step>
[0131] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Yb2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Mn2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. The composition after sintering was Li 5.9 Yb 0.81 Mn 0.09 Zr 0.1 They were weighed in a predetermined stoichiometric ratio in the manner of (BO3)3 and mixed in a mortar and pestle.
[0132] Thereafter, the mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0133] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0134] <Post-calcination step>
[0135] The pre-calcined powder prepared as described above was molded and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 1. The heating temperature was 670° C. and the holding time was 720 minutes.
[0136] [Example 14]
[0137] <Pre-baking step>
[0138] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Yb2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Ga2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. The composition after sintering was Li 5.9 Yb 0.81 Ga 0.09 Zr 0.1They were weighed in a predetermined stoichiometric ratio in the manner of (BO3)3 and mixed in a mortar and pestle.
[0139] Thereafter, the mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0140] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0141] <Post-calcination step>
[0142] The pre-calcined powder prepared as described above was molded and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 1. The heating temperature was 670° C. and the holding time was 720 minutes.
[0143] [Example 15]
[0144] <Pre-baking step>
[0145] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Tm2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. 5.9 Tm 0.810 Al 0.090 Zr 0.100 A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1 except that the weights were adjusted to a predetermined stoichiometric ratio.
[0146] <Post-calcination step>
[0147] The pre-sintered powder prepared as described above was subjected to the same post-baking step as in Example 1 to produce a sintered body. The heating temperature was 670° C. and the holding time was 720 minutes.
[0148] [Example 16]
[0149] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Ho2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. 5.9 Ho 0.810 Al 0.090 Zr 0.100 A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1 except that the weights were adjusted to a predetermined stoichiometric ratio.
[0150] <Post-calcination step>
[0151] The pre-sintered powder prepared as described above was subjected to the same post-baking step as in Example 1 to produce a sintered body. The heating temperature was 670° C. and the holding time was 720 minutes.
[0152] [Example 17]
[0153] <Pre-calcination step>
[0154] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Er2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. The composition after sintering was Li 5.9 Er 0.810 Al 0.090 Zr 0.100 They were weighed in a predetermined stoichiometric ratio in the manner of (BO3)3 and mixed in a mortar and pestle.
[0155] Thereafter, the mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0156] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0157] <Post-calcination step>
[0158] The pre-calcined powder prepared as described above was molded and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 7. The heating temperature was 670° C. and the holding time was 720 minutes.
[0159] [Comparative Example 1]
[0160] <Pre-baking step>
[0161] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Y2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. 5.9 Y 0.810 Al 0.090 Zr 0.100 A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1 except that the weights were adjusted to a predetermined stoichiometric ratio.
[0162] <Post-calcination step>
[0163] The pre-sintered powder prepared as described above was subjected to the same post-baking step as in Example 1 to produce a sintered body. The heating temperature was 670° C. and the holding time was 720 minutes.
[0164] [Comparative Example 2]
[0165] <Pre-baking step>
[0166] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Sm2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. 5.9 Sm 0.810 Al 0.090 Zr0.100 A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1 except that the weights were adjusted to a predetermined stoichiometric ratio.
[0167] <Post-calcination step>
[0168] The pre-sintered powder prepared as described above was subjected to the same post-baking step as in Example 1 to produce a sintered body. The heating temperature was 670° C. and the holding time was 720 minutes.
[0169] [Reference Example 1]
[0170] <Pre-calcination step>
[0171] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Yb2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. 5.900 Yb 0.900 Zr 0.100 They were weighed in a predetermined stoichiometric ratio in the manner of (BO3)3 and mixed in a mortar and pestle.
[0172] Thereafter, the mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0173] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0174] <Post-calcination step>
[0175] The pre-calcined powder prepared as described above was molded and heat-treated in the same manner as in the pre-calcination, thereby producing a sintered body of Reference Example 1. The heating temperature was 650° C., and the holding time was 720 minutes.
[0176] [Reference Example 2]
[0177] <Pre-calcination step>
[0178] Li3BO3 (obtained from Toshima Manufacturing Co., Ltd.), H3BO3 (obtained from Kishida Chemical Co., Ltd.), Y2O3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO2 (obtained from Nippon Denko Co., Ltd.) were provided as raw materials for the solid electrolyte. 5.900 Y 0.900 Zr 0.100 They were weighed in a predetermined stoichiometric ratio in the manner of (BO3)3 and mixed in a mortar and pestle.
[0179] Thereafter, the mixed powder was subjected to cold uniaxial molding using a hydraulic press SSP-10A from Shimadzu Corporation, and heat treated in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0180] The obtained pre-baked body was ground with a mortar and pestle to prepare a pre-baked powder.
[0181] <Post-calcination step>
[0182] The pre-calcined powder prepared as described above was molded and heat-treated in the same manner as in the pre-calcination, thereby producing a sintered body of Reference Example 2. The heating temperature was 650° C., and the holding time was 720 minutes.
[0183] Composition analysis and X-ray diffraction peak measurement were performed on the sintered bodies of Examples 1 to 17, Comparative Examples 1 and 2, and Reference Examples 1 and 2 by the above method. Ion conductivity was measured by the following method. The method for measuring ion conductivity is described below. Table 1 shows the evaluation results obtained.
[0184] ·Measurement of ionic conductivity
[0185] Gold electrodes were deposited on the top and bottom surfaces of each flat sintered body obtained by the post-baking step using a magnetron sputtering system MSP-10 available from Vacuum Device Co., Ltd. to produce samples for AC impedance measurement.
[0186] A potentiostat / galvanostat SI 1287A and a frequency response analyzer 1255B from Solartron Analytical were used for the AC impedance measurements. The measurement conditions were room temperature and a frequency of 1 MHz to 0.1 Hz.
[0187] The resistance of the sintered body was calculated from the complex impedance diagram obtained by impedance measurement. The ion conductivity was determined from the calculated resistance, the thickness of the sintered body, and the electrode area using the following formula.
[0188] Ionic conductivity (S / cm) = sintered body thickness (cm) / (sintered body resistance (Ω) × electrode area (cm) 2 ))
[0189] ·result
[0190] Table 1 shows the stoichiometric amounts of raw materials and the heating temperature during post-baking when producing the solid electrolytes according to Examples 1 to 17 and Comparative Examples 1 and 2, the diffraction peak positions, and the ion conductivity. Figure 1 The relationship between the ion conductivity of each solid electrolyte according to Examples 1 to 17, Comparative Examples 1 and 2, and Reference Examples 1 to 3 included in the first embodiment and the value of the composition x (x1+x2) of the substituting element M is shown. Figure 2 The relationship between the ion conductivity of each solid electrolyte according to Examples 1 to 17 and Comparative Examples 1 and 2 included in the first embodiment and the value of the composition y of the metal element A is shown.
[0191] The results of the above composition analysis show that each sintered body (solid electrolyte) has the elements of the raw materials described in Table 1. The sintered bodies (solid electrolytes) according to Examples 1 to 17 are each solid electrolytes that are successfully densified at a low temperature below 700° C. and exhibit high ion conductivity.
[0192] Figure 3 and Figure 4 The diffraction curves obtained by XRD in the range of 2θ=10° to 40° are shown. It can be seen that the crystal structure of each of Examples 1 to 14 is monoclinic Li6Yb(BO3)3, the crystal structure of Example 15 is monoclinic Li6Er(BO3)3, the crystal structure of Example 16 is monoclinic Li6Ho(BO3)3, and the crystal structure of Example 17 is monoclinic Li6Tm(BO3)3.
[0193] Figure 5 and Figure 6 The diffraction curve obtained by XRD in the range of 2θ=27° or more and 29° or less when R is Yb is shown. It can be seen that the peak positions near the diffraction angles 2θ=28.1° and 28.5° observed in the solid electrolytes according to Examples 1 to 8 are shifted to a higher angle than the peak positions of the solid electrolytes according to Reference Example 1. When the X-ray diffraction graphs of the solid electrolytes according to Examples 1 to 8 are compared with Reference Example 2, it is found that the peak positions near the diffraction angles 2θ=28.1° and 28.5° are almost the same. From these facts, it is believed that the X-ray diffraction graph changes in response to changes in the crystal structure caused by substitution of at least a portion of Yb and the metal element A as a rare earth element by at least one element selected from the group including M.
[0194] Figure 7 X-ray diffraction curves of the solid electrolytes according to Examples 15 to 17 in the range of diffraction angles 2θ=27° or more and 29° or less are shown. It can be seen that the peak positions near the diffraction angles 2θ=28.1° and 28.5° observed in the solid electrolyte according to Example 15 are shifted to higher angles than the respective peak positions of the solid electrolyte according to Reference Example 2. Comparison between the solid electrolyte according to Example 15 and the solid electrolyte according to Reference Example 5 reveals that the peak positions near the diffraction angles 2θ=28.1° and 28.5° are almost the same. These are considered to be changes in the X-ray diffraction curve in response to changes in the crystal structure caused by substitution of at least a portion of the rare earth element Er by at least one element selected from the group including M.
[0195] Similar to Example 15, the solid electrolytes of Examples 16 and 17 also exhibited a peak shift to a higher angle. In the solid electrolytes of Examples 16 and 17, it is considered that the change in the X-ray diffraction curve responds to the change in the crystal structure caused by substitution of at least a part of Ho and Tm as rare earth elements and the metal element A by at least one element selected from the group including M.
[0196] When the ionic conductivity σ is 5×10 -7 In the solid electrolytes according to Examples 1 to 17 with a S / cm or more, as shown in Table 1, it is observed that as the X-ray diffraction angle peak shifts to a wider angle, the double peak diffraction peak shifts to a higher angle peak. That is, it can be read that in the range of 28.0° or more and 29.0° or less, the diffraction angle difference 2θd between the high angle side diffraction peak observed at 28.3° to 29.0° and the low angle side diffraction peak observed at 28.0° to 28.3° increases to 0.416° or more. In other words, the solid electrolyte according to the present embodiment includes a borate containing Li, an element R selected from Yb, Er, Ho, Tm and La, an element A selected from Al, Fe, Mn and Ga, and an element M selected from Zr and Ce. In addition, the solid electrolyte of the present embodiment, in other words, is an electrolyte that exhibits two diffraction peaks within the range of a diffraction angle 2θ of greater than 28.0° and less than 29.0° in XRD using copper Kα rays, wherein the diffraction angle difference 2θd between the high-angle side diffraction peak and the low-angle side diffraction peak is greater than 0.43°.
[0197] The two diffraction peaks observed in the range of diffraction angle 2θ being 27.4° or more and 29.0° or less may also include a multi-peak including three peaks or four peaks, depending on the crystallinity. In this specification, the two diffraction peaks are represented as having one peak on the low angle side and one peak on the high angle side, respectively, separated by a diffraction angle 2θ of 28.3°. In this way, the diffraction peaks are separated by fitting to a double-peak diffraction curve.
[0198] Such a high-angle side diffraction peak is more significantly broadened and shifted to a higher angle than the low-angle side diffraction peak as the composition of the substitution element M increases or as the ion conductivity increases. These results show that the solid electrolyte 44 of the present embodiment has a different crystal structure from the unsubstituted comparative example, so that a variety of crystal structures with distributions of lattice spacing and grain size are mixed.
[0199] In each solid electrolyte having an ion conductivity of 5E-7 (S / cm) or more according to Examples 1 to 17, the atomic concentration ratio [M] / [R]+[A] of the concentration of the substitution element M to the total concentration of the rare earth element R and the metal element A is 0.05 or more and 0.43 or less. In each solid electrolyte having an ion conductivity of 2E-5 (S / cm) or more according to Examples 1 to 15, the atomic concentration ratio [M] / [R]+[A] of the substitution element M to the rare earth element R and the metal element A is 0.11 or more and 0.25 or less.
[0200] In each solid electrolyte having an ion conductivity of 5E-7 (S / cm) or more according to Examples 1 to 17, the atomic concentration ratio [A] / [R] of the metal element A to the rare earth element R is 0.05 or more and 1.00 or less. In each solid electrolyte having an ion conductivity of 2E-5 (S / cm) or more according to Examples 1 to 17, the atomic concentration ratio [A] / [R] of the metal element A to the rare earth element R is 0.11 or more and 0.25 or less.
[0201] [Table 1]
[0202] Table 1
[0203]
[0204] The present invention is not limited to the above-described embodiments, and various changes and modifications can be made within the spirit and scope of the present invention. Therefore, in order to apprise the public of the scope of the present invention, the following claims are made.
[0205] This application claims priority based on Japanese Patent Application No. 2022-104634 filed on Jun. 29, 2022, which is hereby incorporated by reference in its entirety.
[0206] Reference numerals list
[0207] 44 Solid Field Matter
Claims
1. A solid electrolyte comprising a general formula Li 6-x R 1-y-a A y-b M x (BO3)3 represented by oxide, in, In this formula, R is an element selected from Yb, Tm, Ho, Er, and La; A is an element selected from Al, Fe, Mn, and Ga; M is a tetravalent element selected from Zr and Ce; a and b are real numbers satisfying 0 ≤ a, b < 1 and a + b = x; and x and y are real numbers satisfying 0 < x, y < 1.
2. The solid electrolyte according to claim 1, wherein In X-ray diffraction analysis using Cu Kα rays, the solid electrolyte exhibits diffraction peaks in the range where 2θ is 28.0° or more and 29.0° or less, and the diffraction angle difference 2θd between the high-angle-side diffraction peak and the low-angle-side diffraction peak is 0.416° or more.
3. The solid electrolyte according to claim 1 or 2, wherein R is Yb, A contains Al, and in X-ray diffraction analysis using Cu Kα rays, the solid electrolyte exhibits diffraction peaks in the range where 2θ is 28.10° or more and 28.20° or less.
4. The solid electrolyte according to any one of claims 1 to 3, wherein R is Yb, A contains Al, M is Zr, and x satisfies 0 < x < 1.
5. The positive electrode according to any one of claims 1 to 4, comprising the solid electrolyte, a positive electrode active material configured to receive or release lithium ions from or to the electrolyte, and a surface on which the solid electrolyte and the active material are disposed.
6. A secondary battery, comprising: The positive electrode according to claim 5; An electrolyte layer configured to be in contact with the surface and configured to receive or release lithium ions from or to the positive electrode; and A negative electrode in contact with a surface of the electrolyte layer opposite to the side in contact with the surface.
7. The electrolyte layer according to any one of claims 1 to 4, comprising a surface on which the solid electrolyte is disposed.
8. A secondary battery comprising: The electrolyte layer according to claim 7, a positive electrode configured to be in contact with the surface and receive or release lithium ions from or to the electrolyte layer, and a negative electrode in contact with a surface of the electrolyte layer opposite to the surface.
9. A solid electrolyte containing a borate, the borate containing Li, an element R selected from Yb, Er, Ho, Tm, and La, an element A selected from Al, Fe, Mn, and Ga, and an element M selected from Zr, Ce, and Sn.
10. The solid electrolyte according to claim 9, wherein The atomic concentration ratio [M] / ([R] + [A]) of the element M with respect to the total of the element R and the element A is 0.05 or more and 0.43 or less.
11. The solid electrolyte according to claim 10, wherein The atomic concentration ratio [M] / ([R] + [A]) is 0.11 or more and 0.25 or less.
12. The solid electrolyte according to any one of claims 9 to 11, wherein The atomic concentration ratio [A] / [R] of the element A to the element R is 0.05 or more and 0.50 or less.
13. The solid electrolyte according to claim 12, wherein The atomic concentration ratio [A] / [R] of the element A to the element R is 0.11 or more and 0.25 or less.
14. A solid electrolyte comprising a borate, wherein the borate contains Li, an element R selected from Yb, Er, Ho, Tm and La, an element A selected from Al, Fe, Mn and Ga, and an element M selected from Zr and Ce, wherein: In X-ray diffraction analysis using Cu Kα rays, the solid electrolyte exhibits two diffraction peaks in the range where the diffraction angle 2θ is 28.0° or more and 29.0° or less, and the diffraction angle difference 2θd between the high-angle-side diffraction peak and the low-angle-side diffraction peak is 0.416° or more.
15. A solid electrolyte comprising the general formula Li 6-x R 1-y-a A y-b M x (BO3)3 represented by oxide, in, In this formula, R is a rare earth element selected from Yb, Tm, Ho, Er, and La; A is a trivalent element selected from Al, Fe, Mn, and Ga; M is a tetravalent element selected from Zr and Ce; a and b are real numbers satisfying 0 ≤ a, b < 1 and a + b = x; and x and y are real numbers satisfying 0 < x, y < 1.
16. The solid electrolyte according to claim 14, wherein In X-ray diffraction analysis using copper Kα rays, the solid electrolyte exhibits two diffraction peaks in the range where the diffraction angle 2θ is 28.0° or more and 29.0° or less, and the diffraction angle difference 2θd between the high-angle side diffraction peak and the low-angle side diffraction peak is 0.416° or more.
17. The solid electrolyte according to any one of claims 9 to 13, wherein The element M contains Zr.
18. The solid electrolyte according to claim 17, wherein The element M further contains Ce.
19. The solid electrolyte according to any one of claims 9 to 13, wherein The element R contains multiple rare earth elements.
20. The solid electrolyte according to claim 19, wherein The multiple rare earth elements at least include Yb.
21. The solid electrolyte according to claim 9 or 20, wherein The element R contains Yb, A contains Al, and in X-ray diffraction analysis using copper Kα rays, a diffraction peak is exhibited in the range where the diffraction angle 2θ is 28.0° or more and 28.20° or less.
22. The solid electrolyte according to claim 15, wherein R contains Yb, A contains Al, M contains Zr, and x satisfies 0 < x < 1.
23. A positive electrode comprising the solid electrolyte according to any one of claims 9 to 13 and 17 to 20, and a positive electrode active material configured to receive lithium ions from or release lithium ions to the solid electrolyte.
24. The positive electrode according to claim 23, wherein The positive electrode has a surface on which the solid electrolyte and the positive electrode active material are arranged.
25. A secondary battery comprising: The positive electrode according to claim 24; An electrolyte layer configured to be in contact with the surface and configured to receive lithium ions from or release lithium ions to the positive electrode; And A negative electrode in contact with a surface of the electrolyte layer opposite to the side in contact with the surface.
26. An electrolyte layer comprising a surface on which the solid electrolyte according to any one of claims 9 to 13 and 17 to 20 is arranged.
27. A secondary battery comprising the electrolyte layer according to claim 26, a positive electrode configured to be in contact with the surface and receive lithium ions from or release lithium ions to the electrolyte layer, and a negative electrode in contact with a surface of the electrolyte layer opposite to the surface.
Citation Information
Patent Citations
Solid electrolyte and method for producing the same
JP2013037992A
Golf swing analysis system, golf swing analysis method and program
JP2022104634A